2009
DOI: 10.1002/hed.21137
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cell proliferation and glucose uptake in human laryngeal carcinoma cells by antisense oligonucleotides against glucose transporter‐1

Abstract: Glut-1 AS decreases glucose uptake and inhibits the proliferation of Hep-2 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 28 publications
3
48
3
Order By: Relevance
“…HIF-1α and GLUT-1 are the intrinsic hypoxia markers that have been studied the most in various tumours (13)(14)(15)(16)(17)(18). Nevertheless, few studies have investigated the value of HIF-1α (22,23,28,29) or GLUT-1 expression (24,25) alone for the prediction of clinical outcome and survival rate of laryngeal carcinoma and, to the best of our knowledge, there is …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HIF-1α and GLUT-1 are the intrinsic hypoxia markers that have been studied the most in various tumours (13)(14)(15)(16)(17)(18). Nevertheless, few studies have investigated the value of HIF-1α (22,23,28,29) or GLUT-1 expression (24,25) alone for the prediction of clinical outcome and survival rate of laryngeal carcinoma and, to the best of our knowledge, there is …”
Section: Discussionmentioning
confidence: 99%
“…In a previous study of GLUT-1 expression in laryngeal carcinoma, the expression of GLUT-1 mRNA and protein was increased in laryngeal carcinoma Hep-2 cells and an antisense oligonucleotide against GLUT-l mRNA reduced the expression of GLUT-1 mRNA and protein, thus inhibiting glucose uptake and cell growth in Hep-2 cells (25). Based on these results, it was suggested that GLUT-1 is a potential therapeutic target for strategies designed to inhibit the progression of laryngeal cancer (25).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The human genes encoding these proteins are named GLUT-l to -5 and GLUT-7 to -13; GLUT-6 and -14 are now known to be pseudogenes. Of the 14 isoforms, GLUT-1 appears to be the most ubiquitously distributed (10,12,13). Increased GLUT-1 levels and glucose uptake correlate with increased cellular growth and proliferation (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Of the 14 isoforms, GLUT-1 appears to be the most ubiquitously distributed (10,12,13). Increased GLUT-1 levels and glucose uptake correlate with increased cellular growth and proliferation (12,13). This isoform is overexpressed in many human cancer cells, and its appearance is correlated with aggressive biological behavior (10,12).…”
Section: Introductionmentioning
confidence: 99%